ANALISIS PENGARUH PERCEIVED VALUE TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING DITINJAU DARI MANAJEMEN BISNIS SYARIAH (Studi Pada Pengguna Scarlet di Bandar Lampung) - Yulistia Devi; Ghina Ulfah Saefurrohman; Liya Ermawati; Nurwahyu Ningsih (Pustaka Peradaban, 2023)
Research on the effect of perceived value on customer loyalty have not shown consistent results. Research in different products provides different conclusions. So, it is necessary to re-research various product fields to test the relationship between these concepts. This study aims to examine the relationship between perceived value and loyalty mediated by the variable consumer satisfaction in skincare products. The skincare product in question is Scarlet, which currently has the largest market share in Indonesia. This study uses quantitative data analysis. The sample was selected by probability sampling technique with a total sample of 100 people. Hypothesis testing is done by path analysis. Research finds that: (1) perceived value has a significant effect on loyalty. (2) perceived value has a significant influence on customer satisfaction. (3) satisfaction has a significant influence on customer loyalty. (4) Consumer satisfaction mediates the relationship between perceived value and consumer loyalty.